Continental Connections: Changing Temperature, Wind and Precipitation Advance the Postbreeding Roosting Phenology of Avian Aerial Insectivores - Yuting Deng; Birgen Haest; Maria C. T. D. Belotti; Wenlong Zhao; Gustavo Perez; Elske K. Tielens; Daniel R. Sheldon; Subhransu Maji; Jeffrey F. Kelly; Kyle G. Horton (Global Ecology and Biogeography, 2025)
Aim Migratory birds are under threat by climate change. Successfully conserving them requires knowing which climatic factors drive changes in their migratory behaviour. Weather conditions may directly or indirectly affect the temporally disjointed life history stages of migratory birds, including the breeding, roosting and nonbreeding stages. However, the influences of these broad‐scale patterns are often not studied together. Coupling migratory bird movements estimated using weather radar (NEXRAD) with long‐term and large‐scale environmental data allows us to overcome these spatiotemporal uncertainties. Here, we assess environmental drivers of the phenology of postbreeding roosting of aerial insectivores in the Great Lakes region (USA) by evaluating predictors during the months leading up to roosting across species' ranges. Location Northern United States and Canada. Time Period 21‐year (2000–2020). Major Taxa Studied Avian aerial insectivores. Methods We conducted a spatially explicit time‐window analysis to examine the effects of 17 gridded weather and vegetation variables on swallow peak roosting phenology in the Great Lakes, making minimal ecological assumptions. Results We found that peak roosting timing is paced by both local conditions (headwind at 850 hPa) at the Great Lakes and distant conditions (minimum temperature, precipitation rate and specific humidity) at the likely breeding and stopover sites, with warmer temperatures advancing, headwind delaying and high precipitation advancing the phenophases. Time windows selected for the possible breeding and stopover sites are mostly before or around the time of roosting, with one exception during wintertime. Main Conclusions Although climatic shifts play a significant role in driving variation in phenology, for migratory species, the proximate driver can originate hundreds to thousands of kilometres away, and potentially months prior. Our study illuminates these far‐reaching patterns in aerial insectivores, enhancing our grasp of migration ecology and paving the way for a more comprehensive understanding of hemispheric animal movements.

A machine learning classification of meteorite spectra applied to understanding asteroids - M. Darby Dyar; Sydney M. Wallace; Thomas H. Burbine; Daniel R. Sheldon (Icarus, 2023)

Quantifying long‐term phenological patterns of aerial insectivores roosting in the Great Lakes region using weather surveillance radar - Yuting Deng; Maria Carolina T. D. Belotti; Wenlong Zhao; Zezhou Cheng; Gustavo Perez; Elske Tielens; Victoria F. Simons; Daniel R. Sheldon; Subhransu Maji; Jeffrey F. Kelly; Kyle G. Horton (Global Change Biology, 2023)
Organisms have been shifting their timing of life history events (phenology) in response to changes in the emergence of resources induced by climate change. Yet understanding these patterns at large scales and across long time series is often challenging. Here we used the US weather surveillance radar network to collect data on the timing of communal swallow and martin roosts and evaluate the scale of phenological shifts and its potential association with temperature. The discrete morning departures of these aggregated aerial insectivores from ground‐based roosting locations are detected by radars around sunrise. For the first time, we applied a machine learning algorithm to automatically detect and track these large‐scale behaviors. We used 21 years of data from 12 weather surveillance radar stations in the Great Lakes region to quantify the phenology in roosting behavior of aerial insectivores at three spatial levels: local roost cluster, radar station, and across the Great Lakes region. We show that their peak roosting activity timing has advanced by 2.26 days per decade at the regional scale. Similar signals of advancement were found at the station scale, but not at the local roost cluster scale. Air temperature trends in the Great Lakes region during the active roosting period were predictive of later stages of roosting phenology trends (75% and 90% passage dates). Our study represents one of the longest‐term broad‐scale phenology examinations of avian aerial insectivore species responding to environmental change and provides a stepping stone for examining potential phenological mismatches across trophic levels at broad spatial scales.

Groundwater cooling of a supercomputer in Perth, Western Australia: hydrogeological simulations and thermal sustainability - Heather A. Sheldon; Peter M. Schaubs; Praveen K. Rachakonda; Michael G. Trefry; Lynn B. Reid; Daniel R. Lester; Guy Metcalfe; Thomas Poulet; Klaus Regenauer-Lieb (Hydrogeology Journal, 2015)

Elevated summer temperatures delay spawning and reduce redd construction for resident brook trout ( S alvelinus fontinalis ) - Dana R. Warren; Jason M. Robinson; Daniel C. Josephson; Daniel R. Sheldon; Clifford E. Kraft (Global Change Biology, 2012)
Redd (nest) surveys for resident brook trout ( S alvelinus fontinalis ) were conducted annually in a mountain lake in northern New York for 11 years with multiple surveys conducted during the spawning season in eight of those years. Repeated surveys throughout the spawning season allowed us to fit an individually based parametric model and estimate the day of year on which spawning was initiated, reached its midpoint, and ended during each year. Spawning phenology was then assessed relative to (1) mean of maximum daily air temperature and (2) mean of maximum daily water temperature at the lake bottom during summer in each year using a linear model. Elevated temperatures in summer were correlated with a delay in spawning and a reduction in the total number of redds constructed. Increasing the summer mean of maximum daily air temperatures by 1 °C delayed spawning by approximately 1 week and decreased the total number of redds constructed by nearly 65. Lake spawning brook trout select redd sites based on the presence of discharging groundwater that is relatively constant in temperature within and across years, leading to relatively consistent egg incubation times. Therefore, delayed spawning is likely to delay fry emergence, which could influence emergence synchrony with prey items. This work highlights non‐lethal and sub‐lethal effects of elevated summer temperatures on native resident salmonids in aquatic environments with limited thermal refugia.